Design of Dual Space Inquiry framework for facilitating flexible learning in digital technology era - Novitra, Fuja; Abdullah, Mohd Nor Syahrir; Özdemir, Erdogan; Riyasni, Selma; Emiliannur; Festiyed; Metra, Pol (International journal of educational research open, 2025)
Mixed learning that offers flexibility is a current requirement. However, the challenge lies in ensuring that these approaches effectively accommodate interactive and practical elements, especially in physics education. This research aims to design a conceptual framework of the Dual Space Inquiry for facilitating flexible learning in basic physics course. An educational design research (EDR) approach was used to develop and validate the Dual Space Inquiry framework comprising three phases: analysis and exploration; design and construction; and evaluation and reflection. This research involved 253 students and 20 experts and practitioners. The findings highlighted the urgency of implementing a mixed learning framework that combines face-to-face and online learning methods in physics education contexts to optimize learning outcomes. These results became the basis for the design of the Dual Space Inquiry Framework which emphasizes flexibility, humanism, and student-centered. Furthermore, the results of expert and practitioner judgment showed that the framework's validity is in the high category (v-values=0.770). Based on the results, it is concluded that an approach that combines online and offline learning with inquiry activities integration in a balanced manner is recommended for optimal learning outcomes for physics education. The Dual Space Inquiry Framework, with its high validity, is a valuable framework for lecturers in physics and other science fields to enhance learning quality and adapt to the digital technology era.